Human Agents vs. GPU-Powered GenAI in Customer Service Platforms - Amaan Javed (Journal of Computer Science and Technology Studies, 2025)
GPU-powered Generative AI (GenAI) presents a transformative alternative to traditional human agent models in modern customer service environments. The evolution from basic ticketing systems to sophisticated AI-augmented platforms has enabled technology capable of understanding context and generating human-like responses at scale. GenAI implementations deliver substantial value through case summarization, response suggestion, and knowledge retrieval, particularly in high-volume environments with recognizable interaction patterns. Performance advantages include reduced handle times, increased first-contact resolution, and improved agent satisfaction, though success depends critically on maintaining response latencies below key thresholds. The economics of GPU-powered solutions demonstrate favorable cost structures compared to human-only approaches, especially when optimized through techniques like batching, quantization, and knowledge distillation. A comprehensive decision framework identifies ideal implementation scenarios while recognizing contexts where traditional tools remain preferable. Strategic integration rests on three fundamental pillars: speed, trust, and ROI, requiring a structured roadmap prioritizing incremental value creation. Emerging trends in model architecture, contextual grounding, and multimodal capabilities signal increasingly sophisticated applications where technology augments rather than replaces human capabilities.